Seroprevalence of Hepatitis B, Hepatitis C, and Syphilis Antibodies in Premarital Screening Program - Meshari, Amna M.; Hameed, Lamis A.; Almousawi, Hayat Y. (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Premarital screening is essential for identifying reproductive, genetic, and infectious diseases to prevent long-term health complications in couples and their future offspring. Specific Background: Infections such as hepatitis B (HBV), hepatitis C (HCV), and syphilis pose serious public health risks, particularly in regions with high endemicity, yet data on their prevalence in premarital populations remain limited. Knowledge Gap: Despite mandatory screening policies, seroprevalence data and associated sociodemographic factors among premarital individuals are underreported. Aim: This study aimed to determine the seroprevalence of HBV, HCV, and syphilis antibodies among individuals undergoing premarital screening and to explore related sociodemographic characteristics. Results: Among 1066 randomly selected participants from Basrah in 2017, the highest prevalence was observed for HBV (0.66/1000), followed by HCV (0.59/1000) and syphilis (0.52/1000). Significant associations were found between all infections and gender and occupation, while HBV was significantly related to residence and syphilis to age. Novelty: This study provides updated, large-scale evidence of low but present infection rates and sociodemographic correlations in a premarital cohort. Implications: Findings support the continuation and refinement of premarital screening programs to guide early interventions, inform public health strategies, and reduce transmission risks to spouses and offspring. Highlights: Identifies hidden infections in asymptomatic individuals before marriage. Links sociodemographic factors to infection prevalence. Supports targeted public health interventions through early detection. Keywords: Premarital Screening, Hepatitis B, Hepatitis C, Syphilis, Seroprevalence